Pengaruh pH Terhadap Rendemen Silika Gel dari Kulit Tebu Tibarau (Saccharum spontaneum Linn) Menggunakan Metode Sol-Gel - Ramadhani, Rini; Aini, Syamsi (Departemen Kimia FMIPA UNP, 2023)
Several natural materials containing silica have been widely used to synthesize silica nanoparticles such as bagasse, rice husks, which can be in the form of dry and non consumable strands that function as inner protectors in the form of endospermium and embryos. Tibarau sugarcane is one of the renewable organic materials. The synthesis of silica nanoparticles from sudden sugarcane skin tibarau using the sol-gel method has been carried out, therefore we need to synthesize them from renewable materials as well. One of the renewable materials is organic. Different base materials require different reactions. One of the different synthesis is husk ash wherein, husk ash has amorphous phase characteristics ranging from 20-25o. The results of the synthesis of silica nanoparticles the effect of pH on the yield of silica gel, obtained the optimum pH at pH 8 and the results of the synthesis were characterized by FTIR to determine the functional groups containing silanol and siloxane functional groups and XRD to determine the crystallinity and the formed phase at 2θ = 31,7. Silica nanoparticles from sugarcane husk suddenly have a crystalline phase as well as an amorphous phase.